Convergent neural substrates of inattention in bipolar disorder patients and dopamine transporter‐deficient mice using the 5‐choice CPT. (28th May 2019) - Young, Jared W.; Geyer, Mark A.; Halberstadt, Adam L.; van Enkhuizen, Jordy; Minassian, Arpi; Khan, Asma; Perry, William; Eyler, Lisa T.
Abstract: Objectives: Bipolar disorder (BD) is a debilitating psychiatric illness affecting 2%‐5% of the population. Although mania is the cardinal feature of BD, inattention and related cognitive dysfunction are observed across all stages. Since cognitive dysfunction confers poor functional outcome in patients, understanding the relevant neural mechanisms remains key to developing novel‐targeted therapeutics. Methods: The 5‐choice continuous performance test (5C‐CPT) is a mouse and fMRI‐compatible human attentional task, requiring responding to target stimuli while inhibiting responding to nontarget stimuli, as in clinical CPTs. This task was used to delineate systems‐level neural deficits in BD contributing to inattentive performance in human subjects with BD as well as mouse models with either parietal cortex (PC) lesions or reduced dopamine transporter (DAT) expression. Results: Mania BD participants exhibited severe 5C‐CPT impairment. Euthymic BD patients exhibited modestly impaired 5C‐CPT. High impulsivity BD subjects exhibited reduced PC activation during target and nontarget responding compared with healthy participants. In mice, bilateral PC lesions impaired both target and nontarget responding. In the DAT knockdown mouse model of BD mania, knockdown mice exhibited severely impaired 5C‐CPT performance versus wildtype littermates. Conclusions: These data support the role of the PC in inattention in BD—specifically regarding identifying the appropriate response to target vs nontarget stimuli. Moreover, the findings indicate that severely reduced DAT function/hyperdopaminergia recreates the attentional deficits observed in BD mania patients. Determining the contribution of DAT in the PC to attention may provide a future target for treatment development.